ChemInform Abstract: Aerobic Multicomponent Tandem Synthesis of 3‐Sulfenylimidazo[1, 2‐a]pyridines from Ketones, 2‐Aminopyridines, and Disulfides. Issue 11 (18th March 2014) - Ge, Wenlei; Zhu, Xun; Wei, Yunyang
Abstract This protocol is also amenable to the preparation of 3‐selenated imidazopyridines and works even without the presence of a disulfide or diselenide giving high flexibility of the substituent in 3‐position.